If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -2) + -10 = 5x + -2 Reorder the terms: 3(-2 + 4x) + -10 = 5x + -2 (-2 * 3 + 4x * 3) + -10 = 5x + -2 (-6 + 12x) + -10 = 5x + -2 Reorder the terms: -6 + -10 + 12x = 5x + -2 Combine like terms: -6 + -10 = -16 -16 + 12x = 5x + -2 Reorder the terms: -16 + 12x = -2 + 5x Solving -16 + 12x = -2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -16 + 12x + -5x = -2 + 5x + -5x Combine like terms: 12x + -5x = 7x -16 + 7x = -2 + 5x + -5x Combine like terms: 5x + -5x = 0 -16 + 7x = -2 + 0 -16 + 7x = -2 Add '16' to each side of the equation. -16 + 16 + 7x = -2 + 16 Combine like terms: -16 + 16 = 0 0 + 7x = -2 + 16 7x = -2 + 16 Combine like terms: -2 + 16 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| -4x+6=4x+2 | | 3x+6=9X+10 | | 8x-(4x+20)=8 | | 2(h+5)-3(h-2)=5(2h+1) | | 3(x-6)=x-22 | | (25+3x)=(2x+30) | | 17x-114=13x+62 | | 2x-8+9x=8x+6-4x | | 5x+x=24000000 | | 3(3y+3)=7+3y | | 2(x-4)+7=4x-2(3+x) | | -4y-1y=-3 | | 24-3h=0 | | 4y-4(2y+2)=1-4(5-y) | | Y+2=5(x+1) | | -6+m=35 | | (X^2-120x+900)+(-2x^2+30x)=equation | | 3(x-4)=x-20 | | -2(t-3)-8=-4(t+1) | | 7x+3y=-30 | | 6h+1=25 | | 11d-17-10d=5 | | 6x+10+2x-10=90 | | y=(-2)+y | | xy-6x-4=y | | 25v^2=40v | | -4x+(-9)x+19=21+16 | | 26=20*ln(1.8x+4) | | x+(x+17)+(3x-24)=598 | | 9-(2y-5)=1-3y | | 8a+40=6 | | 6x+8-9x=14-18x+15x-6 |